Rape culture: A socio-historical, legal and human analysis - Hermes, Emely Elisa; Griza, Laura dos Santos; Schröder, Maiara; Puhl , Mário José (Seven Editora, 2023)
The article addresses the theme of rape culture from a socio-historical, legal, and human perspective, in the Brazilian context at the beginning of the twenty-first century. It analyzes the historical and social process of the formation of this culture, and its current legal reflexes in Brazil having as references the recognition and institution of Human Rights, either by international conventions or by the current Federal Constitution. The objective is to list how national legislation typifies the practice of rape. The research problem is why the practices of rape constitute an act of violence, an attack on the sexual dignity of the victims. Rape is configured as a practice of violence, defined as an action that attacks the physical and psychological integrity of the person, the violation of the human dignity of someone (CHAUÍ, 1997) and the sexual dignity of the individual (BRASIL, 2013; 1996).  To carry out the research and the textual elaboration, the deductive approach method was followed, the methods of documentary and bibliographic procedure, configuring an activity of a basic nature and data treatment qualitatively, with explanatory purposes. The phenomenon of rape, manifested in a culture, is a violent practice that attacks human dignity, and sexual dignity. Human practice opposes the current legal order, as well as the declarations coming from the United Nations, which recognize and seek to protect and guarantee the physical and mental integrity of all individuals due to the defense of human dignity. DOI:https://doi.org/10.56238/alookdevelopv1-124